A case of Guillain-Barré syndrome in a 24-year-old man - Das, Saikat; Shil, Rahul; Paul, Moumita; Chandra M. S., Girish (International Journal Of Community Medicine And Public Health, 2026)
Guillain-Barré syndrome (GBS) is an acute, immune-mediated neurological disorder that affects approximately 1.2 to 2.3 individuals per 100,000 population annually, with notable regional and seasonal variations. In recent years, an increase in reported cases in certain regions of India has highlighted its emerging public health significance. GBS is characterized by rapid onset of muscle weakness and can progress to severe paralysis if not promptly managed. Early diagnosis and timely therapeutic interventions, such as immunotherapy and supportive care, are essential to improve patient outcomes and reduce the risk of long-term disability. This case report describes a 24-year-old male diagnosed with severe motor axonal polyneuropathy, a variant of GBS associated with more aggressive progression. Following a thorough clinical evaluation and diagnostic investigations, the patient was initiated on plasmapheresis. Currently, his condition is stable, with no further neurological deterioration, indicating a positive response to treatment and ongoing medical management.